Pembelajaran Sains Berbasis Proyek Melalui Eksperimen Bubble Sabun Bertema Belalai Gajah dalam Menstimulasi Rasa Ingin Tahu Anak Usia Dini (studi kasus di TK Al Qodar) - Atik wahidatul Hasanah (CV Edujavare Publishing, 2026)
Curiosity is one of the fundamental dispositions that supports children's cognitive development and scientific thinking during early childhood. However, science learning in many early childhood education settings remains dominated by teacher-centered activities, limiting opportunities for children to explore, investigate, and construct knowledge through direct experience. This study aims to describe the implementation of project-based science learning through the Elephant Trunk Soap Bubble Experiment in stimulating young children's curiosity at TK Al Qodar. The study employed a qualitative approach using a case study design. Research participants consisted of the principal, classroom teachers, and children who participated in the learning project. Data were collected through participant observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. Data credibility was ensured through source triangulation, technique triangulation, member checking, and prolonged engagement. The findings indicate that project-based science learning creates meaningful learning experiences that encourage children to actively ask questions, observe scientific phenomena, test various ideas, collaborate with peers, and communicate their findings during the learning process. The integration of storytelling, imaginative play, and contextual experimentation through the elephant trunk theme increased children's engagement, sustained attention, and willingness to repeat investigations, reflecting the emergence of scientific curiosity. The findings also demonstrate that teachers' roles as facilitators and the provision of authentic exploration opportunities significantly support children's cognitive engagement and inquiry behaviors. This study concludes that project-based science learning through the Elephant Trunk Soap Bubble Experiment effectively stimulates curiosity by integrating play, scientific exploration, and collaborative learning into a meaningful educational experience. The study contributes to the development of constructivist-based science learning practices in early childhood education and provides practical insights for designing innovative, child-centered science activities.